PROVIDING EFFICIENCY OF LEGAL REGULATION THROUGH EFFICIENT LAW ENFORCEMENT AND QUALITATIVE CONDITION OF LEGISLATION (Journal of actual problems of jurisprudence, 2019)
In this article the author analyses an interdependence of the legal norms usage and quality of the legal norms. The author cameto the conclusion that usage of the legal norms depends on the state of the legislation. Such dependence, in its turn, influences theprovision of effectiveness of the legal regulation, which can not be ignored nowadays.